Effects of standardized mindfulness programs on burnout: a systematic review and original analysis from randomized controlled trials - Dyna Shoker; Dyna Shoker; Laura Desmet; Nelly Ledoux; Anne Héron; Anne Héron (Frontiers Media S.A., 2024)
According to the World Health Organization (WHO), burnout is a syndrome conceptualized as resulting from chronic occupational stress that has not been successfully managed. It is characterized by emotional exhaustion, cynicism toward work, and a lack of personal accomplishment at work. Recent WHO guidelines on mental health suggest that mindfulness could have beneficial effects in a professional environment, but to the best of our knowledge, there is currently no study that has made a large inventory of research focused specifically on the effects of standardized programs on burnout. Which professional populations have already been studied? What are the characteristics of the programs? Have studies shown a significant effect and on what indicator?ObjectiveTo assess the effects of standardized programs of mindfulness on burnout, we carried out a systematic review using an exhaustive inventory of the international literature based on randomized controlled trials (RCTs).MethodsThe articles were selected according to PRISMA recommendations. The Embase, PubMed/MEDLINE, EBSCOhost, HAL databases were searched with the keywords "mindfulness," "burnout," and "randomized" in the title and abstract of each article. The data were all collected in an Excel spreadsheet and analyzed in pivot tables, which were then presented in graphs and maps.ResultsA total of 49 RCTs were thus selected, the majority of which were of good methodological quality, of American origin (43% of studies), concerned professionals in the health sector (64% of participants included), and mostly women (76%). The RCTs assessed the effects of 31 different mindfulness programs, mostly with the Maslach Burnout Inventory (78% of RCTs). More than two-thirds of RCTs (67%) showed a significant beneficial effect on burnout measurement indicators, with emotional exhaustion being the most impacted component.ConclusionThis systematic review shows that mindfulness-based interventions could be approaches of choice to prevent emotional distress of burnout. Further studies are still needed to determine which type of program is best suited to impact the two other components of burnout.